Comparación in vitro de filtración marginal entre ionómeros vítreos como selladores de fisura - Sly, Gabriela (2011)
The aim of this study was evaluate in vitro the marginal microleakage of two glass ionomer materials used as pit-and-fissure sealants. Thirty healthy premolars, extracted for orthodontic treatment were randomly assigned in to II groups (n=15) and sealant by two glass ionomer (Group I: Fuji VII and Group II: Fuji IX). All teeth conserved in artificial saliva (NAF) for 10 days, were thermocycled (250 cycles; 5ºC, 37ºC and 60ºC), isolated, immersed in 2% alcohol solution gentian violet blue dye for 4 h. After washed, they were included in acrylic resin and sectioned longitudinally in buccolingual direction by cutting device (Miniton de Struers). Samples were analyzed for leakage using light microscope (Olympus BX-60M).  A semi-quantitative ranked scale from Williams & Winter was used to score dye penetration. Results: Group I was distributed as follows Grade 1: 1 and Grade 3: 14 (Mean 2.87 Median 3, SD 0.52). Group II was distributed: Grade 0: 4, Grade 1: 3 Grade 2: 2 and Grade 3: 6. (Mean 1.67, Median 2, SD 1.29). Fisher Exact Test showed statistically significant differences between materials (p = 0.006). From these results, we concluded that Fuji IX showed better marginal seal than Fuji VII, when used as pit- fissure sealant. The aim of this study was evaluate in vitro the marginal microleakage of two glass ionomer materials used as pit-and-fissure sealants. Thirty healthy premolars, extracted for orthodontic treatment were randomly assigned in to II groups (n=15) and sealant by two glass ionomer (Group I: Fuji VII and Group II: Fuji IX). All teeth conserved in artificial saliva (NAF) for 10 days, were thermocycled (250 cycles; 5ºC, 37ºC and 60ºC), isolated, immersed in 2% alcohol solution gentian violet blue dye for 4 h. After washed, they were included in acrylic resin and sectioned longitudinally in buccolingual direction by cutting device (Miniton de Struers). Samples were analyzed for leakage using light microscope (Olympus BX-60M).  A semi-quantitative ranked scale from Williams & Winter was used to score dye penetration. Results: Group I was distributed as follows Grade 1: 1 and Grade 3: 14 (Mean 2.87 Median 3, SD 0.52). Group II was distributed: Grade 0: 4, Grade 1: 3 Grade 2: 2 and Grade 3: 6. (Mean 1.67, Median 2, SD 1.29). Fisher Exact Test showed statistically significant differences between materials (p = 0.006). From these results, we concluded that Fuji IX showed better marginal seal than Fuji VII, when used as pit- fissure sealant. The aim of this study was evaluate in vitro the marginal microleakage of two glass ionomer materials used as pit-and-fissure sealants. Thirty healthy premolars, extracted for orthodontic treatment were randomly assigned in to II groups (n=15) and sealant by two glass ionomer (Group I: Fuji VII and Group II: Fuji IX). All teeth conserved in artificial saliva (NAF) for 10 days, were thermocycled (250 cycles; 5ºC, 37ºC and 60ºC), isolated, immersed in 2% alcohol solution gentian violet blue dye for 4 h. After washed, they were included in acrylic resin and sectioned longitudinally in buccolingual direction by cutting device (Miniton de Struers). Samples were analyzed for leakage using light microscope (Olympus BX-60M).  A semi-quantitative ranked scale from Williams & Winter was used to score dye penetration. Results: Group I was distributed as follows Grade 1: 1 and Grade 3: 14 (Mean 2.87 Median 3, SD 0.52). Group II was distributed: Grade 0: 4, Grade 1: 3 Grade 2: 2 and Grade 3: 6. (Mean 1.67, Median 2, SD 1.29). Fisher Exact Test showed statistically significant differences between materials (p = 0.006). From these results, we concluded that Fuji IX showed better marginal seal than Fuji VII, when used as pit- fissure sealant.